PL01.3 The genomics of chlamydia trachomatis: a constant surprise. (13th September 2015) - Thomson, Nick
Abstract : Chlamydia trachomatis is an important human pathogen, responsible for diseases ranging from trachoma to sexually transmitted infections that cause substantial morbidity in developed as well as developing countries. In the UK alone Chlamydia is estimated to cost the National Health System up to 100 million pounds every year (www.chlamydiascreening.nhs.uk ). OmpA genotyping is the most widely used typing scheme for Chlamydia with the ocular genotypes represented by A to C, urogenital genotypes D to K and for LGV its L1-L3. Studies from all over the world show that the most common urogenital genotypes are E, F and D. This has led to the pervasive view that that during the last few decades, the overall distributions urogenital of C. trachomatis genovars throughout the world has been relatively stable. Moreover, there are a large number of epidemiological studies that have used ompA-type as a marker to infer relatedness between isolates and compare disease presentations between genotypes. Looking across them all there is almost an equal number of epidemiological studies that have shown an association between genotype and the hosts: age, gender, number of sexual partners, or clinical symptoms, compared to the number of studies that have not. However, recently whole genome sequence has challenged much of our evidence, hypothesis, views and preconceptions about many bacterial pathogens, but especially Chlamydia. We now have accurate phylogenies that reveal how the different 'types' of C. trachomatis actually relate to each other showing us the typing protocols based on a single region or small number of genomic loci that we have been using should be treated with caution, Why? Because C. trachomatis has been shown to be a highly dynamic bacterium exchanging huge portions of its DNA with members of its own species regardless of what body sight we think those isolates are restricted to or have a tropism for. This may not only explain why there is such as disparity in studies looking for correlations between ompA-genotype and disease presentation but also shows us that there are in fact still real opportunities to discover features of the basic biology of this fascinating bacterium. But perhaps more than this, through a combination of the ever-increasing burden of disease, recent advances in technology and molecular tools for chlamydial research, it shows us that there has never been a better time to be a Chlamydiologist.